E-Service Quality and Brand Image on Buying Interest - Muhammad Andrew (Jurnal Sekretaris dan Administrasi Bisnis, 2019)
With the expanding of internet access, more and more activities related to buying or selling goods and services done through e-commerce. One of the e-commerce platforms in Indonesia, Shopee Indonesia, is here to meet the needs of Indonesian consumers in buying and selling online. But there are some cases showing that customers get unsatisfactory e-service quality. These consumers complain in various online media to voice their disappointment at unsatisfactory e-service providers. This affects the buying interest of other consumers who read these customers’ complaints. Besides ruined by unsatisfactory services given by its vendors, the shopee's brand image also affects consumers who want to shop online through Shopee, in this case related to consumer buying interest. There are many ways to see how the brand image is good or not. As in the Top Brand Indonesia site, where Indonesian Shopee is not included in the Top Brand Indonesia buying and selling category. Responding to this, this studi has the aims to see and measure the extent of the influence of e-service quality and brand image on consumers' buying interest in PT Shopee International Indonesia. By doing so, data are analyzed using the classic assumption test, product moment correlation coefficient analysis, multiple linear regression analysis, determination coefficient and partial hypothesis test (T test) and simultaneous hypothesis test (Test F). The results of this study indicated that e-service quality has a significant effect on buying interest with a significance value of 0.037 which is from F table of 3.0901. Whereas the relationship between independent and dependent variables is 29.9%, which is indicated by the value of Adusted R Square of 0.299. This means that the remaining 71.1% is influenced by other variables not examined in this study. Keywords: brand image, buying interest shopee indonesia, e-service quality